Pre-marital screening for Thalassaemia: is it relevant in Malaysia? - Mohd Yusof, Muhammad Al-Fateh; Mohd Din, Amrieel Nuqman; Shahreel Riza, Aina Safiyya; Ghazali, Sara Nur Sofea; Shahrom, Nurul Hazirah; Nordin, Nurul Farhana; Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association (MIMPA), 2025)
The IIUM MBBS SEMINAR SERIES are e-books based on Phase 1 Kulliyyah of Medicine, IIUM, MBBS student seminar presentations. As part of the curriculum, all students are required to present one seminar. Topics covered are varied and not necessarily related to medicine. This e-book is based on the topic of thalassaemia. It touches on the the disease, its clinical manifestations, screening tests, and the relevance of pre-marital screening in Malaysia.